Syndrome of Inappropriate Antidiuretic Hormone Secretion Associated with Pramipexole in a Patient with Parkinson’s Disease - Yoonjae Choi; Jeong Jin Park; Na Young Ryoo; So-Hyun Kim; Changseok Song; Im-Tae Han; Chang-Gi Hong; Choong Kun Ha; Seong Hye Choi (Journal of Movement Disorders, 2011)
The syndrome of inappropriate antidiuretic hormone secretion (SIADH) can be caused by a variety of drugs. Dopaminergic drugs might enhance the secretion of the antidiuretic hormone arginine vasopressin by reducing γ-amino butyric acid release through the dopaminergic receptor in supraoptic nucleus. A 75-year-old woman with Parkinson’s disease developed asthenia, delirium, aggravated parkinsonian symptoms, and hypotonic hyponatremia along with the diagnostic criteria for SIADH during dose escalation of pramipexole. After pramipexole withdrawal, these symptoms disappeared, and sodium levels returned to normal values. The serum sodium levels of patients receiving pramipexole should be monitored, especially during dose escalation.